Pembuatan Game Hack-and-Slash dengan Deck Building 2D “Need More Gold” - Harley Leo Liman; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
“Need More Gold” is a hack-and-slash dan deck-building game build for PC platform. Player will play as a boy exploring an abandon castle. “Need More Gold” use keyboard as the main control to move the character, cards dan consumables. In this game, players will play as a character who will explore an old castle and search for abandoned treasures. Players will fight many monsters, collect objects to defeat existing bosses until the player finally reaches the deepest part of the castle and finds the treasure. This game created by Unity game engine with C# as the programming language. Testing has been done by Black Box Testing, Alpha Testing by lecturer and Beta Testing by sharing and filling questionaires to 30 respondents. The result is the game has normal difficulty level for people who have played at least one of the genre and hard difficulty level for those who haven’t played before.